Exploring the Dynamics among Eco-friendly Vehicles, Sustainability, and Consumer Purchasing Behavior - Narci, Muhammed Talha (International Journal of Energy Economics and Policy, 2026)
This study explores the impact of sustainability perceptions of environmentally friendly vehicles on individuals' purchasing decisions using a quantitative research methodology. Data were collected through a survey conducted in Turkey in May and June 2025, yielding 419 valid responses. The survey comprised four sections: demographic information, Sustainability Awareness Scale, Sustainable Consumption Behavior Scale, and Purchase Behavior Scale. Initially, confirmatory factor analysis (CFA) indicated that the sustainability awareness and sustainable consumption behavior scales were not statistically suitable. Consequently, exploratory factor analysis (EFA) was conducted, resulting in a revised one-dimensional "Sustainability Scale" and a 15-item Sustainable Consumption Behavior Scale with three subdimensions: "Sustainable Awareness," "Saving," and "Reuse." Path analysis, performed through structural equation modeling, examined the relationships between these variables. The analysis revealed that sustainability awareness significantly influences all dimensions of purchasing behavior, while the reuse dimension of sustainable consumption behavior impacts all subdimensions of purchasing behavior. However, the savings dimension only affects word-of-mouth communication, while environmental awareness only affects the willingness to pay more. The study’s findings contribute to understanding how sustainability perceptions shape consumer behavior, offering insights for marketing strategies aimed at promoting environmentally friendly vehicles.